Evaluation of Lanuse/Landcover Dynamics in Vishav Watershed of Kashmir Valley (J&K) - Nanda, Aadil Manzoor; Hamid, Aadil; Ahmed, Pervez; Kanth, Tasawoor A. (National Geographical Journal of India, 2022)
Not available